Performance Comparison of Text Based Game Prototypes Using GTmetrix - Ida Bagus Kerthyayana Manuaba (Journal of Games, Game Art, and Gamification, 2021)
Access to the internet and the advanced of technology allow people to experience in playing a game, not limited to their game console or through a PC, but also through their gadget like mobile-phones. Based on our initial study, a text-based game prototype has shown its potentiality as an alternative media to enhance youth literacy. The prototype has been developed in web-based platform that allow users to play this game through their mobile-phone. This paper describes an extend study to explore on how well the performance of text- based game prototype, when it was run online through a mobile device. For this purpose, a testing tool, named â€œGTmetrixâ€ is used to review the performance of mobile device that run two different text-based game prototype platforms, which are Quest and Ink Platforms. For further comparison, this paper also included additional test scenario to see the performance of these two prototype platforms through a desktop device. These testing was conducted through different mobile network speeds (2G/3G/4G). Two different test approaches, PageSpeed and YSlow, were used to analyze the performance. Based on the results, it can be concluded that both prototype platforms are still compatible to be played through mobile devices, with Ink platform perform slightly better compare to the Quest platform in several test setting.